Greening Growth: The Revealed Comparative Advantage of Indian Transport Sector Emissions - Khatoon, Syeeda; Mehdi, Syed Asghar (Journal of Environmental Management and Tourism, 2026)
Greening growth requires aligning economic expansion with environmental sustainability, a challenge that is particularly acute for rapidly growing economies such as India. The transport sector plays a dual role in this transition: it is a critical enabler of productivity, mobility, and tourism-led growth, while simultaneously emerging as one of the fastest-growing sources of greenhouse gas (GHG) emissions. This study examines India’s transport-sector ((Mobile combustion – road, rail, ship & aviation) emissions in a global comparative perspective by applying the Revealed Comparative Advantage (RCA) framework to transport-related GHG emissions (CO2, CH4, N2O, and F-gases) for the period 1970–2023, using EDGAR data. The analysis compares India’s emission intensity relative to world averages and major emitting countries, including China, the United States, Japan, Russia, and Canada, as well as international aviation and shipping. Findings indicate that while India’s relative environmental burden remained below the global benchmark until the mid-2000s, its RCA in transport-sector emissions has exceeded unity thereafter, coinciding with accelerated economic growth, motorisation, urbanisation, and rising aviation demand. Road transport and aviation emerge as the dominant contributors, with international transport activities approaching global average emission intensities. The results highlight that India and China currently exhibit a revealed comparative disadvantage in greening transport growth relative to advanced economies that have begun to decouple transport emissions from economic expansion. The study underscores the urgency of integrated mitigation strategies, including rapid electrification of road transport, modal shifts towards rail, expansion of low-carbon public transport, deployment of sustainable aviation fuels, and stronger regulatory and market-based instruments. Aligning transport decarbonisation with tourism growth and broader development goals is essential for India to achieve green growth without compromising mobility and economic aspirations.